The Determinant of Tax Awareness in Higher Education and its Impact on Compliance - Ikhwanudin, Ikhwanudin; Hermana, Budi; Indrayani, Emmy (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to analyze the elements affecting the compliance of individual taxpayers in Indonesia. This study will focus on the role of taxpayer awareness and tax center activities in affecting compliance. Method: In this research, the author intends to examine the variables in question, in which a quantitative approach will be used. In this case, the author used a structured questionnaire to collect the primary data, which was distributed to 285 respondents who were selected using the purposive sampling method. This research is based on a taxonomy of three exogenous variables: tax knowledge, ease of administration, and law enforcement, which is in turn is impacted by a mediating variable, taxpayer awareness, a moderating variable of tax center activity, and an endogenous variable of taxpayer compliance. The data collected will be processed using descriptive statistics and analyzed using Structural Equation Modeling (SEM-PLS). Results: Law enforcement, tax knowledge, and ease of administration increases taxpayer awareness and compliance. It has been shown that taxpayer awareness mediates the relationship between these three variables and compliance. Tax center activities moderate the relationship between tax knowledge and awareness, but do not moderate the relationship of ease of administration and law enforcement on tax awareness. Novelty: This research is innovative because it incorporates tax center activity both as a moderating variable and taxpayer awareness as a mediating variable within a single structural model. More specifically, this study aids in the empirical understanding of the tax center’s limitations, which seem to be more effective in reinforcing the educative (knowledge) dimension rather than the administrative/law enforcement dimension.